Post-Treatment Ulceration and Bleeding After Cyanoacrylate Injection of Duodenal Varices. Issue 3 (17th March 2020) - Radlinski, Mark; Fie, Taylor; Richhart, Raymond; Wentworth, Brian; Caldwell, Stephen; Henry, Zachary
ABSTRACT: We report a case of recurrent gastrointestinal bleeding in the setting of diffuse duodenal and colorectal varices. These varices were secondary to either congenital absence of the portal vein or chronic occlusion of the portal vein leading to cavernous transformation of a collateral network of varices. He was acutely managed with injection of N-butyl-2-cyanoacrylate into a large complex of duodenal varices. His hospital course was complicated by a postprocedural gastrointestinal bleed within the first 24 hours after the procedure arising from a new duodenal ulcer at the site of injection, likely secondary to ischemia after obliteration of the varices.